Исследования некрополя Пантикапея-Боспора в 2009 г. - Зинько, Е.А. (Археологічні дослідження в Україні, 2010)
Results of excavations at the necropolis of Panticapaeum-Bosporus on the northern slope of the Mithridates Mount are presented. The 5th c. underground crypt 44 of «The System of 2003» was studied.